Influence Branding , Brand Awareness and Brand Image To Consumer Loyalty to the Muslim Fashion Brand Nadheera Luxury - Putri Ariska Maulidina; Rina Rachmawati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Study This aim For analyze the influence of branding, brand awareness, and image brand to loyalty consumers . In competition growing business​ strict , company sued have an effective marketing strategy For maintain consumers . Branding plays a role in form identity and differentiation brand , brand awareness helps consumer recognize and remember brand , whereas image brand reflect perception as well as level trust consumer to brand . This study uses a quantitative approach with a survey method on consumers as respondents. Data were analyzed using multiple linear regression analysis to test the influence of variables partially and simultaneously. The results of the study indicate that the variables branding (X1), brand awareness (X2), and brand image (X3) have a positive and significant effect on consumer loyalty with a significance value of less than 5% ( α < 0.05). The results of the multiple linear regression analysis show that the three variables simultaneously contribute 57.6% to consumer loyalty. This finding indicates that the stronger the branding, the higher the level of awareness and positive brand image, the more consumer loyalty to a brand will increase. Therefore, companies are advised to manage these three aspects in an integrated and sustainable manner to create long-term consumer loyalty.